Local dimensions of the Second World War in Southeastern Europe - Bougarel, Xavier; Grandits, Hannes 1966-; Vulesica, Marija 1978- (Mass violence in modern history, 2019)
"This book deals with the Second World War in Southeastern Europe from the perspective of conditions on the ground during the conflict. The focus is on the reshaping of ethnic and religious groups in wartime, on the 'top-down' and 'bottom-up' dynamics of mass violence, and on the local dimensions of the Holocaust. The approach breaks with the national narratives and 'top-down' political and military histories that continue to be the predominant paradigms for World War Two in this part of Europe"--